Efficient modification method for automotive trim composite material

By integrating UV absorber and hindered amine stabilizers with modified ASA resin and SAN resin, the method addresses photodegradation issues in automotive interior materials, enhancing photostability and mechanical performance.

CN120310153AActive Publication Date: 2025-07-15YANGZHOU HANJIANG YANGZI AUTOMOTIVE INTERIOR ACCESSORIES CO L
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510445809.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2025-07-15
Estimated Expiration
2045-04-10

AI Technical Summary

Technical Problem

Polymer materials in automotive interiors are prone to photooxidation reactions under long-term direct sunlight, resulting in molecular chain breakage, yellowing and mechanical properties degradation, affecting the user experience.

Method used

Through chemical reaction, the ultraviolet absorber basson 1789 and the hindered amine light stabilizer precursor tetramethylpiperidone are functionally integrated at the molecular level to prepare the light stabilizer and compound it with the modified ASA resin and SAN resin to form a modified ASA emulsion, and finally mix it with the SAN resin to prepare the automotive interior composite.

Benefits of technology

It significantly improves the light stability and weather resistance of the composite material, reduces the migration loss of light stabilizer, and improves the impact resistance and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to an efficient modification method for an automotive trim composite material, and belongs to the technical field of composite materials. According to the preparation method, an ultraviolet light absorber Basone 1789 and a hindered amine light stabilizer precursor tetramethyl piperidone are functionally integrated on a molecular level through chemical reaction, and an active methylene structure of the Basone 1789 and a carbonyl structure of the tetramethyl piperidone are subjected to Knoevenagel reaction under the action of an organic amine catalyst to obtain the novel light stabilizer. The preparation method simplifies the synthesis steps of preparing the light stabilizer from tetramethylpiperidone, strengthens the synergistic effect between the ultraviolet light absorber and the light stabilizer, effectively solves the problems of yellowing and embrittlement caused by easy photooxidative degradation of SAN resin exposed to sunlight for a long time through compounding of ASA resin and SAN resin, improves the weather resistance of the SAN resin, and has a wide application prospect. And the impact resistance and weather resistance of the automotive trim are further improved while the rigidity of the SAN resin is reserved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and specifically, relates to an efficient modification method for automotive interior composite materials. Background Art

[0002] With the development of the automotive industry, modern automobiles are often equipped with transparent skylights. The skylights greatly improve the driving experience of users and can also achieve a comprehensive balance of temperature regulation and light control. However, the more abundant light conditions also pose higher requirements for the weather resistance of automotive interior materials. Under long-term direct sunlight, the polymer materials in automotive interiors are prone to photo-oxidation reactions, resulting in the breakage of molecular chains, surface yellowing, fading, and a decline in mechanical properties, seriously affecting the long-term use experience of automotive interiors. Based on this, the present invention provides an efficient modification method for automotive interior composite materials. Summary of the Invention

[0003] The purpose of the present invention is to provide an efficient modification method for automotive interior composite materials to solve the problems mentioned in the above background art.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] An efficient modification method for automotive interior composite materials includes the following steps:

[0006] First step: By mass, dissolve 2 parts of Tinuvin 1789, 0.8 - 1.2 parts of tetramethylpiperidone, and 0.05 - 0.1 part of catalyst in an organic solvent and stir evenly. Control the system temperature at 40 - 110 °C for reaction, then perform vacuum distillation and recrystallization to obtain a light stabilizer.

[0007] Second step: By mass, add 10 - 14 parts of butyl acrylate, 0.4 - 0.6 part of emulsifier, 0.04 - 0.16 part of initiator, 0.2 - 0.5 part of crosslinking agent, and 24 - 36 parts of deionized water into a reaction vessel, continuously stir and mix, introduce nitrogen to exhaust the air in the vessel, and control the system temperature at 60 - 80 °C for reaction for 4 - 12 h to obtain polybutyl acrylate seeds.

[0008] Step 3: Take 10 parts by mass of poly(butyl acrylate) seeds, dilute them with deionized water to 8 - 18 times, and add 0.2 - 0.4 parts of emulsifier, 1.2 - 1.8 parts of sodium formaldehyde sulfoxylate, and 0.1 - 0.3 parts of tetrasodium ethylenediaminetetraacetate to the reaction vessel. Control the system temperature at 60 - 80 °C for the reaction. During this period, continuously add dropwise to the reaction vessel a pre-emulsion prepared in advance from 0.5 - 2.2 parts of crosslinking agent, 0.1 - 0.4 parts of oxidant, 80 - 180 parts of butyl acrylate, and 0.3 - 0.5 parts of emulsifier. The dropping time is 1 - 2 h. After the dropping is completed, continue the reaction for 1 - 2 h to obtain a PBA emulsion with large particle size;

[0009] Step 4: Add 0.1 - 0.4 parts of emulsifier, 1 - 1.6 parts of sodium formaldehyde sulfoxylate, and 0.1 - 0.3 parts of tetrasodium ethylenediaminetetraacetate to the PBA emulsion by mass. Control the system temperature at 40 - 70 °C for the reaction. During this period, continuously add dropwise to the reaction vessel a pre-emulsion prepared in advance from 25 - 75 parts of styrene, 10 - 24 parts of acrylonitrile, 0.3 - 0.6 parts of light stabilizer, 0.3 - 0.8 parts of molecular weight regulator, and 0.8 - 1.2 parts of oxidant. The dropping time is 1 - 4 h. After the dropping is completed, continue the reaction for 2 - 8 h to obtain a modified ASA emulsion. After demulsification, washing, filtering, and drying, a modified ASA resin is obtained;

[0010] Step 5: Add 20 - 30 parts of modified ASA resin, 70 - 80 parts of SAN resin, and 0.1 - 0.6 parts of antioxidant by mass to a high-speed mixer, mix evenly, and then extrude and pelletize through a twin-screw extruder to obtain an automotive interior composite material.

[0011] Further, the component of Bassoon 1789 is 4'-tert-butyl-4-methoxydibenzoylmethane.

[0012] Further, the catalyst is an organic amine catalyst, preferably piperidine.

[0013] Further, the emulsifier is one of sodium dodecyl sulfate and sodium dodecyl sulfonate, preferably sodium dodecyl sulfate.

[0014] Further, the initiator is one of potassium persulfate, ammonium persulfate, and sodium persulfate, preferably potassium persulfate.

[0015] Further, the crosslinking agent is one of triallyl isocyanurate, ethylene glycol dimethacrylate, and butanediol diacrylate, preferably triallyl isocyanurate.

[0016] Further, the oxidant is one of cumene hydroperoxide, lauroyl peroxide, and tert-butyl peroxybenzoate, preferably cumene hydroperoxide.

[0017] Further, the molecular weight regulator is one of n-dodecyl mercaptan and tert-dodecyl mercaptan.

[0018] Further, the antioxidant is one of antioxidant 1010, antioxidant 1078, and butylated hydroxyanisole, preferably antioxidant 1010.

[0019] Further, the SAN resin is a styrene-acrylonitrile copolymer, and the styrene content is 70-80 wt%.

[0020] Advantages of the present invention:

[0021] 1) In the present invention, the ultraviolet absorber Basf 1789 and the hindered amine light stabilizer precursor tetramethylpiperidone are functionally integrated at the molecular level through a chemical reaction. A new light stabilizer is obtained by the Knoevenagel reaction of the active methylene structure of Basf 1789 and the carbonyl structure of tetramethylpiperidone under the action of an organic amine catalyst. This simplifies the synthesis steps for preparing the light stabilizer from tetramethylpiperidone, strengthens the synergistic effect between the ultraviolet absorber and the light stabilizer, realizes the synergistic effect of energy conversion (ultraviolet absorber) and free radical blocking (hindered amine light stabilizer), significantly improves the light stability of the composite material. In addition, the prepared light stabilizer contains polymerizable double bonds, which can be combined in the polybutyl acrylate core in the form of chemical bonds, reducing the migration loss of the light stabilizer during processing and use. Finally, the prepared composite material can have long-term weather resistance.

[0022] 2) The SAN resin has good mechanical properties and excellent chemical stability, but it is brittle and has poor weather resistance. In the present invention, by compounding the modified ASA resin and the SAN resin, the modified ASA resin is not easily oxidized and is grafted with a light stabilizer, which can effectively solve the problems of yellowing and embrittlement caused by photooxidative degradation of the SAN resin when it is exposed to sunlight for a long time, improving the weather resistance of the SAN resin. In addition, the ASA resin has good elasticity and similar polarity to the SAN resin, which can further improve the impact resistance of the automotive interior while retaining the mechanical properties of the SAN resin. Specific embodiments

[0023] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.

[0024] Example 1

[0025] A method for efficiently modifying an automotive interior composite material includes the following steps:

[0026] Step 1: By mass fraction, dissolve 2 parts of Basong 1789, 1 part of tetramethylpiperidone, and 0.05 - 0.1 part of piperidine in 40 parts of absolute ethanol and stir evenly. Control the system temperature at 80°C for 1 h. After the reaction, perform vacuum distillation and then recrystallization to obtain a light stabilizer.

[0027] Step 2: By mass fraction, add 12 parts of butyl acrylate, 0.5 part of sodium dodecyl sulfate, 0.1 part of potassium persulfate, 0.35 part of triallyl isocyanurate, and 30 parts of deionized water into a reaction vessel, continuously stir and mix. Pass nitrogen to exhaust the air in the vessel, and control the system temperature at 70°C for 8 h to obtain polybutyl acrylate seeds.

[0028] Step 3: By mass fraction, take out 10 parts of polybutyl acrylate seeds, dilute them with 120 parts of deionized water, and add 0.3 part of sodium dodecyl sulfate, 1.5 parts of sodium formaldehyde sulfoxylate, and 0.2 part of tetrasodium ethylenediaminetetraacetate to the reaction vessel. Control the system temperature at 70°C for the reaction. During this period, continuously add a pre-emulsion prepared in advance from 1.35 parts of triallyl isocyanurate, 0.25 part of cumene hydroperoxide, 130 parts of butyl acrylate, and 0.4 part of sodium dodecyl sulfate to the reaction vessel. The dropping time is 1.5 h. After the dropping is completed, continue the reaction for 1.5 h to obtain a PBA emulsion with large particle size.

[0029] Step 4: By mass fraction, add 0.25 part of sodium dodecyl sulfate, 1.3 parts of sodium formaldehyde sulfoxylate, and 0.2 part of tetrasodium ethylenediaminetetraacetate to the PBA emulsion. Control the system temperature at 55°C for the reaction. During this period, continuously add a pre-emulsion prepared in advance from 50 parts of styrene, 17 parts of acrylonitrile, 0.45 part of light stabilizer, 0.55 part of n-dodecyl mercaptan, and 1 part of cumene hydroperoxide to the reaction vessel. The dropping time is 2.5 h. After the dropping is completed, continue the reaction for 5 h to obtain a modified ASA emulsion. After demulsification, washing, filtering, and drying, a modified ASA resin is obtained.

[0030] Step 5: By mass fraction, add 25 parts of modified ASA resin, 75 parts of SAN resin, and 0.35 part of antioxidant 1010 into a high-speed mixer, mix evenly, and then extrude and pelletize through a twin-screw extruder to obtain an automotive interior composite material.

[0031] Among them, the styrene content of the SAN resin used in this example is 75 wt%.

[0032] Example 2

[0033] An efficient modification method for an automotive interior composite material, comprising the following steps:

[0034] Step 1: By mass fraction, dissolve 2 parts of Basun 1789, 1.2 parts of tetramethylpiperidone, and 0.1 part of pyrrolidine in 45 parts of N,N-dimethylformamide and stir evenly. Control the system temperature at 110 °C, react for 0.5 h, then perform vacuum distillation and recrystallization to obtain a light stabilizer;

[0035] Step 2: By mass fraction, add 14 parts of butyl acrylate, 0.6 part of sodium dodecyl sulfate, 0.04 - 0.16 part of ammonium persulfate, 0.5 part of ethylene glycol dimethacrylate, and 36 parts of deionized water into a reaction vessel, continuously stir and mix, introduce nitrogen to exhaust the air in the vessel, and control the system temperature at 80 °C to react for 12 h to obtain polybutyl acrylate seeds;

[0036] Step 3: By mass fraction, take out 10 parts of polybutyl acrylate seeds, dilute them with 170 parts of deionized water, and add 0.4 part of sodium dodecyl sulfate, 1.8 parts of sodium formaldehyde sulfoxylate, and 0.3 part of tetrasodium ethylenediaminetetraacetate to the reaction vessel. Control the system temperature at 80 °C to react. During this period, continuously drip a pre-emulsion prepared in advance from 2.2 parts of ethylene glycol dimethacrylate, 0.4 part of lauroyl peroxide, 180 parts of butyl acrylate, and 0.5 part of sodium dodecyl sulfate. The dripping time is 2 h. After dripping, continue to react for 2 h to obtain a PBA emulsion with large particle size;

[0037] Step 4: By mass fraction, add 0.4 part of sodium dodecyl sulfate, 1.6 parts of sodium formaldehyde sulfoxylate, and 0.3 part of tetrasodium ethylenediaminetetraacetate to the PBA emulsion. Control the system temperature at 70 °C to react. During this period, continuously drip a pre-emulsion prepared in advance from 75 parts of styrene, 24 parts of acrylonitrile, 0.6 part of light stabilizer, 0.8 part of n-dodecyl mercaptan, and 1.2 parts of lauroyl peroxide. The dripping time is 4 h. After dripping, continue to react for 8 h to obtain a modified ASA emulsion. After demulsification, washing, filtering, and drying, a modified ASA resin is obtained;

[0038] Step 5: By mass fraction, add 30 parts of modified ASA resin, 70 parts of SAN resin, and 0.6 part of antioxidant 1078 into a high-speed mixer, mix evenly, and then extrude and pelletize through a twin-screw extruder to obtain an automotive interior composite material;

[0039] Among them, the styrene content of the SAN resin used in this example is 70 wt%.

[0040] Example 3

[0041] An efficient modification method for an automotive interior composite material, comprising the following steps:

[0042] Step 1: By mass fraction, dissolve 2 parts of Basf 1789, 0.8 parts of tetramethylpiperidone, and 0.05 parts of diethylamine in 60 parts of dichloromethane and stir evenly. Control the system temperature at 40°C, react for 8 hours, then perform vacuum distillation and recrystallization to obtain a light stabilizer;

[0043] Step 2: By mass fraction, add 10 parts of butyl acrylate, 0.4 parts of sodium dodecylsulfonate, 0.04 parts of sodium persulfate, 0.2 parts of butanediol diacrylate, and 24 parts of deionized water into a reaction vessel, continuously stir and mix. Pass in nitrogen to exhaust the air in the vessel, and control the system temperature at 60°C to react for 4 hours to obtain polybutyl acrylate seeds;

[0044] Step 3: By mass fraction, take out 10 parts of polybutyl acrylate seeds, dilute them with 70 parts of deionized water, and add 0.2 parts of sodium dodecylsulfonate, 1.2 parts of sodium formaldehyde sulfoxylate, and 0.1 parts of tetrasodium ethylenediaminetetraacetate to the reaction vessel. Control the system temperature at 60°C to react. During this period, continuously drip-feed a pre-emulsion prepared in advance from 0.5 parts of butanediol diacrylate, 0.1 parts of tert-butyl peroxybenzoate, 80 parts of butyl acrylate, and 0.3 parts of sodium dodecylsulfonate into the reaction vessel. The dripping time is 1 hour. After the dripping is completed, continue to react for 1 hour to obtain a PBA emulsion with large particle size;

[0045] Step 4: By mass fraction, add 0.1 parts of sodium dodecylsulfonate, 1 part of sodium formaldehyde sulfoxylate, and 0.1 parts of tetrasodium ethylenediaminetetraacetate to the PBA emulsion. Control the system temperature at 40°C to react. During this period, continuously drip-feed a pre-emulsion prepared in advance from 25 parts of styrene, 10 parts of acrylonitrile, 0.3 parts of light stabilizer, 0.3 parts of tert-dodecyl mercaptan, and 0.8 parts of tert-butyl peroxybenzoate into the reaction vessel. The dripping time is 1 hour. After the dripping is completed, continue to react for 2 hours to obtain a modified ASA emulsion. After demulsification, washing, filtering, and drying, a modified ASA resin is obtained;

[0046] Step 5: By mass fraction, add 20 parts of modified ASA resin, 80 parts of SAN resin, and 0.1 parts of butylated hydroxyanisole into a high-speed mixer, mix evenly, and then extrude and pelletize through a twin-screw extruder to obtain an automotive interior composite material;

[0047] Among them, the styrene content of the SAN resin used in this example is 80 wt%.

[0048] Example 4

[0049] The difference between this example and Example 1 is that grafting is not carried out, but the light stabilizer is added by blending.

[0050] An efficient modification method for an automotive interior composite material includes the following steps:

[0051] Step 1: Weighing by mass parts, dissolve 2 parts of Tinuvin 1789, 1 part of 4-methylpiperidin-1-one, and 0.05 - 0.1 part of piperidine in 40 parts of absolute ethanol and stir evenly. Control the system temperature at 80 °C for reaction for 1 h. After the reaction, perform vacuum distillation and then recrystallization to obtain a light stabilizer;

[0052] Step 2: Weighing by mass parts, add 12 parts of butyl acrylate, 0.5 part of sodium dodecyl sulfate, 0.1 part of potassium persulfate, 0.35 part of triallyl isocyanurate, and 30 parts of deionized water into a reaction vessel, continuously stir and mix. Pass in nitrogen to exhaust the air in the vessel, and control the system temperature at 70 °C for reaction for 8 h to obtain polybutyl acrylate seeds;

[0053] Step 3: Weighing by mass parts, take out 10 parts of polybutyl acrylate seeds, dilute them with 120 parts of deionized water, and add 0.3 part of sodium dodecyl sulfate, 1.5 parts of sodium formaldehyde sulfoxylate, and 0.2 part of tetrasodium ethylenediaminetetraacetate to the reaction vessel. Control the system temperature at 70 °C for reaction. During this period, continuously add dropwise a pre-emulsion prepared in advance from 1.35 parts of triallyl isocyanurate, 0.25 part of cumene hydroperoxide, 130 parts of butyl acrylate, and 0.4 part of sodium dodecyl sulfate. The dropping time is 1.5 h. After the dropping is completed, continue the reaction for 1.5 h to obtain a PBA emulsion with large particle size;

[0054] Step 4: Weighing by mass parts, add 0.25 part of sodium dodecyl sulfate, 1.3 parts of sodium formaldehyde sulfoxylate, and 0.2 part of tetrasodium ethylenediaminetetraacetate to the PBA emulsion. Control the system temperature at 55 °C for reaction. During this period, continuously add dropwise a pre-emulsion prepared in advance from 50 parts of styrene, 17 parts of acrylonitrile, 0.55 part of n-dodecyl mercaptan, and 1 part of cumene hydroperoxide. The dropping time is 2.5 h. After the dropping is completed, continue the reaction for 5 h to obtain a modified ASA emulsion. After demulsification, washing, filtering, and drying, ASA resin is obtained;

[0055] Step 5: Weighing by mass parts, add 25 parts of ASA resin, 75 parts of SAN resin, 0.45 part of light stabilizer, and 0.35 part of antioxidant 1010 into a high-speed mixer, mix evenly, and then extrude and pelletize through a twin-screw extruder to obtain an automotive interior composite material;

[0056] Among them, the styrene content of the SAN resin used in this example is 75 wt%.

[0057] Example 5

[0058] The difference between this example and Example 1 is that instead of pre-synthesizing the light stabilizer, Tinuvin 1789 and 4-methylpiperidin-1-one are added by blending.

[0059] An efficient modification method for an automotive interior composite material, comprising the following steps:

[0060] Step 1: By mass fraction, add 12 parts of butyl acrylate, 0.5 part of sodium dodecyl sulfate, 0.1 part of potassium persulfate, 0.35 part of triallyl isocyanurate, and 30 parts of deionized water into a reaction vessel, continuously stir and mix them, introduce nitrogen to exhaust the air in the vessel, and control the system temperature at 70 °C for reaction for 8 h to obtain polybutyl acrylate seeds;

[0061] Step 2: By mass fraction, take out 10 parts of polybutyl acrylate seeds, dilute them with 120 parts of deionized water, and add 0.3 part of sodium dodecyl sulfate, 1.5 parts of sodium formaldehyde sulfoxylate, and 0.2 part of tetrasodium ethylenediaminetetraacetate to the reaction vessel. Control the system temperature at 70 °C for reaction. During the reaction, continuously add a pre-emulsion prepared in advance from 1.35 parts of triallyl isocyanurate, 0.25 part of cumene hydroperoxide, 130 parts of butyl acrylate, and 0.4 part of sodium dodecyl sulfate dropwise to the reaction vessel. The dropping time is 1.5 h. After the dropping is completed, continue the reaction for 1.5 h to obtain a PBA emulsion with large particle size;

[0062] Step 3: By mass fraction, add 0.25 part of sodium dodecyl sulfate, 1.3 parts of sodium formaldehyde sulfoxylate, and 0.2 part of tetrasodium ethylenediaminetetraacetate to the PBA emulsion. Control the system temperature at 55 °C for reaction. During the reaction, continuously add a pre-emulsion prepared in advance from 50 parts of styrene, 17 parts of acrylonitrile, 0.55 part of n-dodecyl mercaptan, and 1 part of cumene hydroperoxide dropwise to the reaction vessel. The dropping time is 2.5 h. After the dropping is completed, continue the reaction for 5 h to obtain a modified ASA emulsion. After demulsification, washing, filtration, and drying, ASA resin is obtained;

[0063] Step 4: By mass fraction, add 25 parts of ASA resin, 75 parts of SAN resin, 0.3 part of Basolan 1789, 0.15 part of tetramethylpiperidone, and 0.35 part of antioxidant 1010 into a high-speed mixer, mix them evenly, and then extrude and pelletize them through a twin-screw extruder to obtain an automotive interior composite material;

[0064] Among them, the styrene content of the SAN resin used in this example is 75 wt%.

[0065] Comparative Example 1

[0066] This comparative example is a commercially available ASA resin.

[0067] Experimental Example 1

[0068] The automotive interior composite materials obtained in Examples 1 - 5 were respectively subjected to the following performance tests:

[0069] Impact resistance test: The test was carried out with reference to the national standard GB / T 40440-2021 "Plastics - Extruded sheets of impact-modified acrylonitrile-styrene copolymers (ABS, AEPDS, and ASA) - Requirements and test methods";

[0070] Rockwell hardness test: The test was carried out with reference to the national standard GB / T 3398.2-2008 "Plastics - Determination of hardness - Part 2: Rockwell hardness";

[0071] Tensile strength test: The test was carried out with reference to the national standard GB / T 1040.1-2018 "Plastics - Determination of tensile properties - Part 1: General principles";

[0072] UV resistance test: The accelerated UV aging experiment was carried out with reference to the national standard GB / T 16422.3 "Plastics - Methods of exposure to laboratory light sources - Part 3: Fluorescent UV lamps". The yellowing value ΔE after 4000 h of UV irradiation was tested and recorded. The results of each test are shown in Table 1:

[0073] Table 1

[0074] Project <![CDATA[Impact strength KJ / m 2 > Rockwell hardness Tensile strength MPa △E of 4000 Example 1 14.8 94 72.36 1.45 Example 2 15.2 96 71.62 1.73 Example 3 13.6 91 75.28 2.04 Example 4 14.4 93 72.45 2.67 Example 5 14.1 94 73.12 6.42 Comparative example 1 15.4 98 46.32 2.44

[0075] As can be seen from Table 1, the automotive interior composite materials of the present invention in Examples 1 to 3 have good impact resistance and surface hardness, and good weather resistance.

[0076] The above has introduced in detail an efficient modification method for an automotive interior composite material provided by the present invention. Specific examples are used in this article to elaborate on the principle and implementation manner of the present invention. The description of the above embodiments is only used to help understand the method and its core idea of the present invention, including the best mode, and also enables any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combination method. It should be noted that for those of ordinary skill in the art in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed by the present invention can be combined with each other in any way. The exhaustive description of these combinations is not given in this specification only for the sake of saving space and resources. Therefore, the present invention is not limited to the specific embodiments disclosed in the text, but includes all technical solutions falling within the scope of the claims.

Claims

1. An efficient modification method for automotive interior composite materials, characterized in that It includes the following steps: Synthesis of the light stabilizer: Dissolve bis(2,2,6,6-tetramethylpiperidin-4-yl) sebacate, 4-oxo-2,2,6,6-tetramethylpiperidine, and an organic amine catalyst in an organic solvent, and control the reaction temperature at 40 - 110 °C to carry out the reaction to obtain the light stabilizer; Preparation of the automotive interior composite material: Add an emulsifier, sodium formaldehyde sulfoxylate, tetrasodium ethylenediaminetetraacetate, styrene, acrylonitrile, the light stabilizer, a molecular weight regulator, and an oxidant to the PBA emulsion, and control the system temperature at 40 - 70 °C to carry out the reaction to obtain a modified ASA resin; Blend and extrude the modified ASA resin, SAN resin, and antioxidant to obtain the automotive interior composite material.

2. The high-efficiency modification method of an automotive interior composite material according to claim 1, characterized in that By mass fraction, the mass fractions of the raw materials in the synthesis of the light stabilizer are 2 parts of bis(2,2,6,6-tetramethylpiperidin-4-yl) sebacate, 0.8 - 1.2 parts of 4-oxo-2,2,6,6-tetramethylpiperidine, and 0.05 - 0.1 part of the catalyst.

3. An efficient modification method for an automotive interior composite material according to claim 1, characterized in that, The emulsifier is one of sodium dodecyl sulfate and sodium dodecyl sulfonate.

4. A method for efficiently modifying an automotive interior composite material according to claim 1, characterized in that The initiator is one of potassium persulfate, ammonium persulfate, and sodium persulfate.

5. A method for efficiently modifying an automotive interior composite material according to claim 1, characterized in that, The crosslinking agent is one of triallyl isocyanurate, ethylene glycol dimethacrylate, and butanediol diacrylate.

6. The efficient modification method of an automotive interior composite material according to claim 1, characterized in that, The oxidant is one of cumene hydroperoxide, lauroyl peroxide, and tert-butyl peroxybenzoate.

7. A method for efficiently modifying an automotive interior composite material according to claim 1, characterized in that, The molecular weight regulator is one of n-dodecyl mercaptan and tert-dodecyl mercaptan.

8. An efficient modification method for an automotive interior composite material according to claim 1, characterized in that The SAN resin is a styrene-acrylonitrile copolymer with a styrene content of 70 - 80 wt%.

9. The high-efficiency modification method of an automotive interior composite material according to claim 1, characterized in that, The antioxidant is one of antioxidant 1010, antioxidant 1078, and butylated hydroxyanisole.

Citation Information

Patent Citations

  • UV stabilization of isosorbide polycarbonates

    CN103328570A

  • Chemical modification ASA resin and preparation method and application thereof

    CN105647047A

  • Stabilizer system and its use for stabilizing styrene polymers

    US4110304A

  • Light absorbing polymers

    US5376650A